In an instant immediate solutions to basic business problems - Jack Wilson and Associates Inc. (Chicago : JWA Video)
Summary: This program find anwers to your business situation with the four-volume video training series. It offers methods you can put to work immediately to help turn those business problems into positive business opportunities
vol.1 Dealing with an individual who is late - vol.2 How to be an effective time manager - vol.3 How to give feedback - vol.4 How to deal with closed-mindedness
Host: Anthony Salemi
Keywords: Personnel management; Supervision of employees; Industrial relation